2012
DOI: 10.1136/annrheumdis-2011-200908
|View full text |Cite
|
Sign up to set email alerts
|

Canakinumab for acute gouty arthritis in patients with limited treatment options: results from two randomised, multicentre, active-controlled, double-blind trials and their initial extensions

Abstract: Canakinumab provided significant pain and inflammation relief and reduced the risk of new flares in these patients with acute gouty arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
164
0
19

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(184 citation statements)
references
References 39 publications
1
164
0
19
Order By: Relevance
“…Gout is characterized by short‐term periods of clinically apparent inflammation, separated by periods of subclinical inflammation 5, 23. Low‐grade inflammation also has a major role in the development of CVDs, and elevated levels of C‐reactive protein and interleukin‐6 have been found to be associated with increased cardiovascular risk 24.…”
Section: Discussionmentioning
confidence: 99%
“…Gout is characterized by short‐term periods of clinically apparent inflammation, separated by periods of subclinical inflammation 5, 23. Low‐grade inflammation also has a major role in the development of CVDs, and elevated levels of C‐reactive protein and interleukin‐6 have been found to be associated with increased cardiovascular risk 24.…”
Section: Discussionmentioning
confidence: 99%
“…7 In 2013, canakinumab was approved in Europe for preventing remittent gouty arthritis based on its capacity to suppress painful inflammation in acute gout attacks faster than intramuscular steroid injection. 97 Unlike most other drugs used in gout, canakinumab can also be used in patients with CKD. 98 Interestingly, renal function seems to improve when gout is treated with IL-1 inhibition.…”
Section: Il-1-related Drugs and Clinical Datamentioning
confidence: 99%
“…This study showed canakinumab to have a rapid onset in pain relief and increased the time between a flare, likely attributable to its half-life of 21-28 days [29,32]. More adverse events were noted in the canakinumab group, which included infections, neutropenia, and thrombocytopenia [32]. Another study compared canakinumab (single dose versus four divided doses weekly) versus colchicine 0.5 mg daily for gout prophylaxis during initiation of ULT with allopurinol [43].…”
Section: Canakinumab and Rilonaceptmentioning
confidence: 97%
“…One double-blind study assessed the efficacy and safety of one dose of 150 mg canakinumab against one single dose of triamcinolone injection at baseline and during an acute gout attack in patients frequently flaring with contraindications to use of NSAIDs and/or colchicine [32]. This study showed canakinumab to have a rapid onset in pain relief and increased the time between a flare, likely attributable to its half-life of 21-28 days [29,32]. More adverse events were noted in the canakinumab group, which included infections, neutropenia, and thrombocytopenia [32].…”
Section: Canakinumab and Rilonaceptmentioning
confidence: 99%